Atmospheric concentrations and dry deposition of reactive nitrogen in the state of São Paulo, Brazil - Souza, Mariana de Almeida [UNESP]; Pacheco, Felipe Siqueira; Palandi, Jalusa Aparecida de Leo; Forti, Maria Cristina; Campos, Maria Lucia A.M.; Ometto, Jean Pierre H.B.; Reis, Dayane Cristina Oliveira; de Carvalho Junior, João Andrade [UNESP] (Elsevier, 2020)
Estimates of nitrogen deposition play a key role in better understanding the human impacts on the nitrogen biogeochemical cycle. This paper examines the concentration of reactive nitrogen (Nr) in the atmosphere and the average dry deposition in the state of São Paulo, Brazil. The Nr species that were measured were in the gaseous (NO2, NH3 and HNO3) and particulate phases (NH4+, NO3−). Denuder-based samplers were spatially distributed in six sites to account for different types of land cover and urbanization. Samples were collected over 2 years (2015–2017). The dominant form of inorganic Nr in the atmosphere was the gaseous NO2 at all sampling sites, which represented 79% of the total. The average concentrations of NH3, HNO3, NH4+ and NO3− were 10%, 3%, 6% and 2% of the total Nr, respectively. The average Nr dry deposition in São Paulo State was 10.6 kg N ha−1 yr−1. The highest average deposition of Nr was found in the SP sampling site and is related to intense vehicular traffic, waste management and industrial activities. This work suggests that dry deposition of Nr into the Atlantic Forest next to São Paulo municipality can exceed the critical nitrogen load suggested for most forests. This implies that human activities in the surrounding areas may be affecting the integrity of one of the most important biodiversity hotspots in South America. These results will contribute to improve Nr budget estimates and to advance Nr deposition modelling approaches.
Keywords: Dry deposition; Nitrogen emission; Particulate matter; Reactive nitrogen